2020
DOI: 10.2147/ndt.s239763
|View full text |Cite
|
Sign up to set email alerts
|

<p>Increased Plasma Kynurenic Acid Levels are Associated with Impaired Attention/Vigilance and Social Cognition in Patients with Schizophrenia</p>

Abstract: Preclinical studies have reported that abnormal kynurenic acid (KYNA) may play a role in cognitive deficits. Schizophrenia (SCZ) is characterized by a wide range of cognitive deficits that may evolve from abnormal KYNA. This study aimed to explore the relationship between KYNA and cognitive impairment in SCZ, which has not yet been reported. Methods: We recruited 30 SCZ patients and 34 healthy controls, measured clinical symptoms by using the Positive and Negative Syndrome Scale and performed cognitive tests u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 57 publications
(62 reference statements)
2
8
1
Order By: Relevance
“…Conversely, in schizophrenia elevated KynA is considered to underlie the cognitive deficits such as executive dysfunction, impairments in set shifting and abstract thinking. In preclinical studies, elevation of brain KynA through the genetic or pharmacological knockdown of KMO was shown to induce cognitive abnormalities evocative of schizophrenia, whereas a recent human study found that plasma KynA levels were significantly higher in SCZ patients than in healthy controls (HC) and that these correlated negatively with attention/vigilance and social cognition [ 65 ]. On the other hand, reducing brain KynA through pharmacological inhibition or genetic knockdown of KAT -II improved cognitive functioning possibly through modulation of α7nAChRs and glycine co-agonist site of NMDAR [ 66 ].…”
Section: Kynurenine Pathway and Mood Disordersmentioning
confidence: 99%
“…Conversely, in schizophrenia elevated KynA is considered to underlie the cognitive deficits such as executive dysfunction, impairments in set shifting and abstract thinking. In preclinical studies, elevation of brain KynA through the genetic or pharmacological knockdown of KMO was shown to induce cognitive abnormalities evocative of schizophrenia, whereas a recent human study found that plasma KynA levels were significantly higher in SCZ patients than in healthy controls (HC) and that these correlated negatively with attention/vigilance and social cognition [ 65 ]. On the other hand, reducing brain KynA through pharmacological inhibition or genetic knockdown of KAT -II improved cognitive functioning possibly through modulation of α7nAChRs and glycine co-agonist site of NMDAR [ 66 ].…”
Section: Kynurenine Pathway and Mood Disordersmentioning
confidence: 99%
“…It is among the top 10 global causes of disability 1 . Biomarkers, such as homocysteine (Hcy), kynurenic acid, C-reactive protein, and triiodothyronine, have been shown to be potential risk factors for schizophrenia [2][3][4][5] . Hcy interacts with NMDA receptors, induces apoptosis, triggers oxidative stress, injures mitochondrial function and leads to vascular damage, which played an essantial role in the occurrence and development of schizophrenia 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The fermentation in YNBT400 resulted the most promising approach for KYNA production which reached the highest concentrations (9.146 ± 0.585 mg/L). In comparison to literature data, the maximum concentration of KYNA measured in the post-culture medium was higher than KYNA levels in plasma of healthy subjects (5.8 ng/mL) [ 54 ] and milk of healthy breast-feeding women (3.9–56.6 microg/L) [ 55 ]. In addition, KYNA was detected in artificial baby formulas at lower concentrations (5.0–7.3 microg/L) [ 55 ].…”
Section: Discussionmentioning
confidence: 64%